The Hidden Side of Complement Regulator C4BP: Dissection and Evaluation of Its Immunomodulatory Activity - Serrano, Inmaculada; Luque, Ana; Mitjavila, Francesca; Blom, Anna M.; Rodríguez de Córdoba, Santiago; Vega, M. Cristina; Torras, Joan; Aran, Josep M. (Frontiers in Immunology, 2022)
C4b-binding protein (C4BP) is a well-known regulator of the complement system that holds additional and important activities unrelated to complement inhibition. Recently, we have described a novel immunomodulatory activity in the minor C4BP(beta-) isoform directly acting over inflammatory phagocytes. Here we show that incorporation of the beta-chain to the C4BP alpha-chain oligomer interferes with this immunomodulatory activity of C4BP. Moreover, an oligomeric form including only the complement control protein 6 (CCP6) domain of the C4BP alpha-chain (PRP6-HO7) is sufficient to “reprogram” monocyte-derived DCs (Mo-DCs) from a pro-inflammatory and immunogenic phenotype to an anti-inflammatory and tolerogenic state. PRP6-HO7 lacks complement regulatory activity but retains full immunomodulatory activity over inflammatory Mo-DCs induced by TLRs, characterized by downregulation of relevant surface markers such as CD83, HLA-DR, co-stimulatory molecules such as CD86, CD80 and CD40, and pro-inflammatory cytokines such as IL-12 and TNF-alpha. Furthermore, PRP6-HO7-treated Mo-DCs shows increased endocytosis, significantly reduced CCR7 expression and CCL21-mediated chemotaxis, and prevents T cell alloproliferation. Finally, PRP6-HO7 shows also full immunomodulatory activity over Mo-DCs isolated from lupus nephritis patients with active disease, even without further pro-inflammatory stimulation. Therefore PRP6-HO7, retaining the immunomodulatory activity of C4BP(beta-) and lacking its complement regulatory activity, may represent a promising and novel alternative to treat autoimmune diseases.